Stabilization of Boumkaye’s Drink for an Accessibility in the Markets - Cisse, Oumar Ibn Khatab; Ayessou, Nicolas Cyrille; Ndiaye, Bou; Cisse, Mady; Sakho, Mama; Diop, Codou Mar (European Scientific Journal, ESJ, 2018)
Boumkaye is a fermented drink made from millet, and prepared according to a traditional process from Casamance’s region in Senegal. Still consumed for its anthelmintic properties, Boumkaye is obtained after maturation marked by two stages of fermentation (lactic and alcoholic). The main limits of this drink are the spontaneous nature of the fermentation and its instability. The objectives of this study is to stabilize this drink after fermentation step. For this purpose, an autoclave heat treatment at 120°C/15 minutes scale has been proposed. Two types of sterilized Boumkaye (crude and fermented) were kept at two temperatures (4 and 25°C) for one year follow-up. The sterilization tests on crude Boumkaye and fermented Boumkaye provided excellent microbiological and nutritional quality. No germ was detected during the entire storage period. In addition, Boumkaye beverages can be stored at 25°C (room temperature) for a minimum of one year while preserving all its organoleptic and therapeutic properties. This is a considerable asset for future industrial exploitation.